Myocardial Contrast and Stress Echocardiography: New Frontiers - Paulo Magno Martins Dourado Jeane Mike Tsutsui; Antonio Casella Filho; Larissa de Almeida Dourado; João Paulo de Almeida Dourado; Leonardo Roever; Wilson Mathias Junior (Archive of Biomedical Science and Engineering - Peertechz Publications, 2017)
Stress Echocardiography is an established technique used all over the world as a non invasive evaluation of patients with coronary artery disease (CAD) and also an important method to evaluate myocardial viability and the contractile reserve.  Myocardial contrast echocardiography (MCE) is a well-defi ned technique to improve delineation of the endocardic borders. It has been increasingly used for the assessment of myocardial perfusion, due to the development of techniques which proportionate simultaneous analysis of myocardial perfusion and function in real-time, it also increases the sensitivity of stress testing for the detection of CAD and it distinguishes between stunned and infarcted  yocardium after acute ischemia. The development of new techniques as strain, strain rate, speckle tracking, real time three dimensional, tissue Doppler, second harmonic image and the use of new contrast agents, associated with digital image development brings new lights about stress and contrast echocardiograph and expands its potential use to evaluate CAD. Coronary disease is the main cause of morbidity and mortality in the ocidental world and,according to World Health Organization, it will be the main cause of death throughout the world in the near future. Therefore, in this review, we present the actual level of development of these important techniques in the setting of the CAD.